RETRACTED: NEAT1 enhances MPP+‐induced pyroptosis in a cell model of Parkinson's disease via targeting miR‐5047/YAF2 signaling - Hong Shen; Hui Song; Songlin Wang; Daojing Su; Qiang Sun (Immunity, Inflammation and Disease)
Abstract Purpose Parkinson's disease (PD) is the second most frequent neurodegenerative disease. The aim of our study is to explore the role and the regulatory mechanism of long noncoding RNA (lncRNA) NEAT1 in MPP+‐induced pyroptosis in a cell model of PD. Materials and Methods MPP+‐treated SH‐SY5Y cells were used as an in vitro model of dopaminergic neurons for PD. Expression levels of miR‐5047 and YAF2 mRNA were determined through qRT‐PCR. TUNEL staining was carried out to analyze neuronal apoptosis. Luciferase activity assay was accomplished to analyze the combination of miR‐5047 with NEAT1 or YAF2 3ʹ‐UTR region. Besides, concentrations of IL‐1β and IL‐18 in supernatant samples were analyzed by using ELISA assay. Expression level of proteins were examined through Western blot. Results NEAT1 and YAF2 expression were increased, while miR‐5047 expression was declined in the SH‐SY5Y cells treated with MPP+. NEAT1 was a positively regulator to SH‐SY5Y cells pyroptosis induced by MPP+. In addition, YAF2 was a downstream target of miR‐5047. NEAT1 promoted YAF2 expression via inhibiting miR‐5047. Importantly, the promotion of NEAT1 to SH‐SY5Y cells pyroptosis induced by MPP+ was rescued by miR‐5047 mimic transfection or YAF2 downregulation. Conclusion In conclusion, NEAT1 was increased in MPP+‐induced SH‐SY5Y cells, and it promoted MPP+‐induced pyroptosis through facilitating YAF2 expression by sponging miR‐5047.